Development of Dosimetric Verification System for Patient-Specific Quality Assurance of High-Dose-Rate Brachytherapy - Kang, Sang-Won; Chung, Jin-Beom; Kim, Kyeong-Hyeon; Choi, Chang Heon; Kang, Seonghee; Shin, Dong-Seok; Cho, Woong; Eom, Kuen-Yong; Park, Hae-Jin; Kim, Jin-Young; Song, Changhoon; Kim, In Ah; et al. (Frontiers in Oncology, 2021)
Purpose: The aim of this study was to develop a dosimetric verification system (DVS) using a solid phantom for patient-specific quality assurance (QA) of high-dose-rate brachytherapy (HDR-BT). Methods: The proposed DVS consists of three parts: dose measurement, dose calculation, and analysis. All the dose measurements were performed using EBT3 film and a solid phantom. The solid phantom made of acrylonitrile butadiene styrene (ABS, density = 1.04 g/cm3) was used to measure the dose distribution. To improve the accuracy of dose calculation by using the solid phantom, a conversion factor (CF(r)) according to the radial distance between the water and the solid phantom material was determined by Monte Carlo simulations. In addition, an independent dose calculation program (IDCP) was developed by applying the obtained CF(r). To validate the DVS, dosimetric verification was performed using gamma analysis with 3% dose difference and 3 mm distance-to-agreement criterion for three simulated cases: single dwell position, elliptical dose distribution, and concave elliptical dose distribution. In addition, the possibility of applying the DVS in the high-dose range (up to 15 Gy) was evaluated. Results: The CF(r) between the ABS and water phantom was 0.88 at 0.5 cm. The factor gradually increased with increasing radial distance and converged to 1.08 at 6.0 cm. The point doses 1 cm below the source were 400 cGy in the treatment planning system (TPS), 373.73 cGy in IDCP, and 370.48 cGy in film measurement. The gamma passing rates of dose distributions obtained from TPS and IDCP compared with the dose distribution measured by the film for the simulated cases were 99.41% and 100% for the single dwell position, 96.80% and 100% for the elliptical dose distribution, 88.91% and 99.70% for the concave elliptical dose distribution, respectively. For the high-dose range, the gamma passing rates in the dose distributions between the DVS and measurements were above 98% and higher than those between TPS and measurements. Conclusion: The proposed DVS is applicable for dosimetric verification of HDR-BT, as confirmed through simulated cases for various doses.